Source-Independent Amplitude-Semblance Full-Waveform Inversion Using a Hybrid Time- and Frequency-Domain Approach (Communications in Computational Physics, 2020)
Full-waveform inversion is a promising tool to produce accurate and high-resolution subsurface models. Conventional full-waveform inversion requires an accurate estimation of the source wavelet, and its computational cost is high. We develop anovel source-independent full-waveform inversion method using a hybrid time- andfrequency-domain scheme to avoid the requirement of source wavelet estimation andto reduce the computational cost. We employ an amplitude-semblance objective function to not only effectively remove the source wavelet effect on full-waveform inversion, but also to eliminate the impact of the inconsistency of source wavelets amongdifferent shots gathers on full-waveform inversion. To reduce the high computationalcost of full-waveform inversion in the time domain, we implement our new algorithmusing a hybrid time- and frequency-domain approach. The forward and backwardwave propagation operations are conducted in the time domain, while the frequency-domain wavefields are obtained during modeling using the discrete-time Fourier transform. The inversion process is conducted in the frequency domain for selected frequencies. We verify our method using synthetic seismic data for the Marmousi model. Theresults demonstrate that our novel source-independent full-waveform inversion produces accurate velocity models even if the source signature is incorrect. In addition,our method can significantly reduce the computational time using the hybrid time- and frequency-domain approach compared to the conventional full-waveform inversion in the time domain.
Keywords: Amplitude semblance; full-waveform inversion; hybrid time and frequency domain; source independent; source wavelet.